2017
DOI: 10.1002/mbo3.508
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of c‐di‐GMP turnover proteins modulate semi‐constitutive rdar biofilm formation in commensal and uropathogenic Escherichia coli

Abstract: Agar plate‐based biofilm of enterobacteria like Escherichia coli is characterized by expression of the extracellular matrix components amyloid curli and cellulose exopolysaccharide, which can be visually enhanced upon addition of the dye Congo Red, resulting in a red, dry, and rough (rdar) colony morphology. Expression of the rdar morphotype depends on the transcriptional regulator CsgD and occurs predominantly at ambient temperature in model strains. In contrast, commensal and pathogenic isolates frequently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 99 publications
1
55
0
Order By: Relevance
“…The swimming motility of ECOR31, though, was not altered upon either overexpression or deletion of csgD compared to the ECOR31 wild-type (Fig. S2A), suggesting swimming motility of ECOR31 to be csgD independent under the assay conditions used in this work (37).…”
Section: Resultsmentioning
confidence: 80%
“…The swimming motility of ECOR31, though, was not altered upon either overexpression or deletion of csgD compared to the ECOR31 wild-type (Fig. S2A), suggesting swimming motility of ECOR31 to be csgD independent under the assay conditions used in this work (37).…”
Section: Resultsmentioning
confidence: 80%
“…Although we could demonstrate convergent evolution of GGDEF domains with the same N-terminal sensing domain within a panel of enterobacterial species, 40 uncoupling of domain homology from the identity of the N-terminal sensory domain and downstream EAL domain occurs readily in natural isolates. 41 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…In this work, we initially characterized a commensal representative of the ST10 clonal complex closely related to E. coli K-12. This strain produces a rdar biofilm morphotype at 28°C ( Figure S2; (Cimdins et al, 2017b)) and harbors an IncY plasmid with the previously identified TLPQC/LHR locus that mediates tolerance toward temporal exposure to lethal temperature and additional cargo genes involved in detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike E. coli K-12, Fec10 displays a full red, dry, and rough (rdar) morphotype, a distinct biofilm colony phenotype characterized by the production of the exopolysaccharide cellulose and amyloid curli fimbriae as extracellular matrix components at ambient temperature ( Figure S2; Cimdins et al, 2017b). Fec10 is a member of the ST10 strain complex, which opens up the opportunity to document adaptation of a member of the abundant phylogroup A/ST10 E. coli subgroup to post-industrial human beings.…”
Section: The Commensal Isolate Fec10 Is a Modern Member Of The E Cmentioning
confidence: 99%
See 1 more Smart Citation